Mild hypothermia reduces cardiac post-ischemic reactive hyperemia - Olivecrona, Goran K; Götberg, Matthias; Harnek, Jan; Van der Pals, Jesper; Erlinge, David (BMC cardiovascular disorders, 2007)
In experimentally induced myocardial infarction, mild hypothermia (33-35 degrees C) is beneficial if applied prior to ischemia or reperfusion. Hypothermia, when applied after reperfusion seems to confer little or no benefit. The mechanism by which hypothermia exerts its cell-protective effect during cardiac ischemia remains unclear. It has been hypothesized that hypothermia reduces the reperfusion damage; the additional damage incurred upon the myocardium during reperfusion. Reperfusion results in a massive increase in blood flow, reactive hyperemia, which may contribute to reperfusion damage. We postulated that hypothermia could attenuate the post-ischemic reactive hyperemia. Sixteen 25-30 kg pigs, in a closed chest model, were anesthetized and temperature was established in all pigs at 37 degrees C using an intravascular cooling catheter. The 16 pigs were then randomized to hypothermia (34 degrees C) or control (37 degrees C). The left main coronary artery was then catheterized with a PCI guiding catheter. A Doppler flow wire was placed in the mid part of the LAD and a PCI balloon was then positioned proximal to the Doppler wire but distal to the first diagonal branch. The LAD was then occluded for ten minutes in all pigs. Coronary blood flow was measured before, during and after ischemia/reperfusion. The peak flow seen during post-ischemic reactive hyperemia (during the first minutes of reperfusion) was significantly reduced by 43 % (p < 0.01) in hypothermic pigs compared to controls. Mild hypothermia significantly reduces post-ischemic hyperemia in a closed chest pig model. The reduction of reactive hyperemia during reperfusion may have an impact on cardiac reperfusion injury.